Encyclopedia of Hydrological Sciences 2005
DOI: 10.1002/0470848944.hsa003
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Process

Abstract: Water, its movement, changes of state, and chemistry, is fundamental to the nature of planet Earth. It is involved in the most important processes near the surface and supports life as we know it. Hydrological sciences potentially address all aspects of water movement and transformation, although with major divisions between hydrology, which is essentially focused on the principle of conservation of mass; hydraulics, based on conservation of momentum (Newton's laws of motion); and meteorology, based on the law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…The channel precipitation, which can be treated as direct runoff, can provide an important component of rapid response to storms (Kirkby, 2005). The proportion of streamflow supplied by the channel precipitation can vary with the intensity and the duration of rainfall.…”
Section: Direct Channel Precipitationmentioning
confidence: 99%
“…The channel precipitation, which can be treated as direct runoff, can provide an important component of rapid response to storms (Kirkby, 2005). The proportion of streamflow supplied by the channel precipitation can vary with the intensity and the duration of rainfall.…”
Section: Direct Channel Precipitationmentioning
confidence: 99%
“…However, process-based studies at both hillslope and catchment scales have demonstrated that in these environments runoff may be also produced as the result of infiltration excess overland flow, especially in areas regarded as impervious or of low permeability because of human activities (Jordan 1994). The hydrological systems are complex and show significant seasonality, such that the dominant processes may experience changes throughout the year (Kirkby 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This seasonality significantly changes the dominant processes through the year (Kirkby, 2005) and makes these rivers particularly vulnerable to anthropogenic pressure. Temporary rivers have been exploited by mankind for millennia because they represent an important source of water in semiarid areas.…”
Section: Introductionmentioning
confidence: 99%